MENINGKATKAN HASIL BELAJAR MATEMATIKA PENGUKURAN (SATUAN PANJANG) DENGAN ALAT PERAGA TANGGA SATUAN PADA SISWA KELAS IV B SDN KEBONSARI I SURABAYA - Zulfani Ainaya; Delia Indrawati; Ganda Riswanto; Sri Yuniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted in class IV B at SDN Kebonsari I Surabaya with the aim of finding out the effect of using teaching aids in Mathematics learning, especially in Measurement material. It was found that student learning outcomes were low, mainly due to teacher-centered learning methods and the minimal use of teaching aids. It is feared that this condition will further reduce student learning outcomes. This research suggests the use of teaching aids to improve mathematics learning outcomes. The long measuring unit ladder prop is used and proven to be effective in improving learning outcomes and student activities. The research results showed a significant improvement, with the average learning outcomes increasing from 68.57% at the beginning of cycle I to 92.50% at the end of cycle II. The use of teaching aids makes learning more interesting and easy to understand. This teaching aid has a significant positive impact on students' learning outcomes, making them more active and enthusiastic, and making it easier to understand the concept of measuring length. It is hoped that the results of this research will become a reference for teachers in improving the quality of Mathematics learning in elementary schools.